Pengenalan dan Pembelajaran Asuransi Melalui Media Online, Sarana Pendukung Program 1000 Aktuaris bagi Masyarakat Indonesia - Hidayat, Agus Sofian Eka (Insan Kreasi Media, 2023)
The low number of representatives from insurance ownership in Indonesia and the lack of achievement of an equal number of actuaries in Indonesia shows the low literacy of the importance of insurance and insurance science. Insurance is an important thing for the community, to face the risk of both death, loss, and health risks. To improve community literacy, seminars and learning are needed that can be accessed easily and cheaply, one of which is using the media YouTube. The results of this service activity have a positive impact on the community, both in terms of understanding insurance terms and knowledge about actuarial fields. It is hoped that more seminars and training activities that are integrated with technology can be carried out to support an increase in the percentage of the number of insurance owners in Indonesia as well as the number of actuaries in Indonesia